Hermeneutic understanding of the Incarnation and the Eucharist: Paul Celan’s Tenebrae and the interpretive nature of communion through body, blood and image - Andrzej Wierciński (Przestrzenie Teorii)
Carnal hermeneutics shows that pre-thematic bodily hermeneutics can complement cognitive hermeneutics. The thematization of sacramental imagination is an essential part of such an approach. Carnal hermeneutics finds new ways of showing how imagination inhabits our bodies and reflects on the emancipatory possibilities that are hidden in the process of maintaining and crossing the various boundaries that constitute our identity. Carnal reading is both reception and creation, i.e., it is not a reading into something but a reading from something. The act of interpreting Paul Celan’s Tenebrae is an exercise in a diacritical hermeneutics of communion and prayer, which contributes to the self-awakening of existence by elucidating the fundamental structures of our understanding of being.